SIR Corner and YBR Foundations Study Aid benefit UMP students - Siti Nur Azwin, Zulkapri (UMPSA, 2023)
PAYA BESAR, 12 June 2023 - The presence of the ‘Serambi Ilmu Rakyat’ (SIR – People's Knowledge) Corner at the Universiti Malaysia Pahang (UMP) Library will be an important value-added feature to enhance comprehensive access to information resources for education and research at UMP.